Derived from an improbable dialogue - Alvarado Ugarte, Hernán (2013)
Karl Marx died in 1883, when Freud was 27. At age 43, only 16 years later, Sigmund finished nothing less than “The Interpretation of Dreams”, a work that launched his discovery of the unconscious. Therefore, it is possible that they had exchanged a couple of letters and that Marx mentioned the exchange in a letter to Engels. Some believe that this is unlikely and that there is no sufficient evidence to establish it as a historical fact. Others defend that these letters did exist and that a copy of at least one of them still remains, in addition to a theory on how they were lost and later found. Using one of these letters from Marx to Freud and taking advantage of the uncertainty, a number of insights are proposed herein based on the work of these two giants of human intelligence, by the means of a fictitious dialogue. This letter is taken literally, whether truth or fiction, and its content is used to multiply and stretch its meanings. This literary game allows for the discussion of epistemological matters such as fetishism and alienation, critical meta-psychology and its materialistic foundation, as well as the unconscious, topic that brings both works together just as much as it separates them. As it is well known, the relationship between them has continued to be both tense and intense; it has not been put off and it surely deserves adding more wood to the fire…